Pembuatan Sistem Informasi Administrasi Pada PT. Galoeh Husada Farma - Winardy Hertanto; Djoni Haryadi Setiabudi; I Gede Agus Widyadana (Jurnal Infra, 2016)
Along with the times, companies need to perform data processing systems, in particular distribution company that sells drugs need an information system to prevent a lack of good control of products in order to avoid out of stock.Application created by using the programming language PHP, Javascript, Ajax, JQuery, and use MySQL as a database. In making the application, administration information system that is created using the FIFO method so that, the first unit were purchased will be first sold and this method is particularly suited to the type of company that distribute medicines to the entire territory of East Java and the outer islands.The final result of making the application of administration information system, which is system that are created using the FIFO method, still cannot resolve a problem about goods that are often used interchangeably when the flow in and out physically in the company.